Chemical Composition and Fatty Acids of Glodok Fish by High Thermal Processing - Sri Purwaningsih; Ella Salamah; Reza Dewantoro (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2014)
Glodok is an economically underrated fish with a high nutrient content. The research aims to study the changes on chemical composition, fatty acids, omega-6 and omega-3 ratio in glodok muscle after processing with different methods of boiling, steaming, and boiling with addition of salt (3%). The results showed that the treatment (boiling, steaming, and boiling with addition of salt) gives a significant effect (α=0.05) in water content, ash, lipid content, nervonat acid, linoleic acid, arachidonic acid, EPA, and DHA. The best processing method was steaming. The ratio of omega-3 and omega-6 in fresh glodok fish was 2,1:1, which is higher than WHO recommendation of 0,6:1,7.Keywords: chemical composition, fatty acid, glodok fish, processing